An application of a parametric transducer to measure acoustic absorption of a living green wall. (February 2019) - Romanova, Anna; Horoshenkov, Kirill V.; Hurrell, Alistair
Abstract: This work reports on a new method to measure the absorption coefficient of a Living Green Wall (LGW) in-situ . A highly directional parametric transducer and acoustic intensity probe are used to make this method robust against background noise and unwanted reflections. This method is tested under controlled laboratory conditions and in-situ on a real green wall. The methods is compared favourably against impedance tube data obtained for porous media which properties are relatively easy to measure using a standard laboratory setup. The new method is an alternative to the ISO354-2003 and CEN/TS 1793-5:2016 standard methods to measure acoustic absorption of materials.